Avaliação da estratégia saúde da família na capital potiguar - Melo, Cynthia de Freitas (2013)
This research aimed to evaluate the Family Health Strategy (FHS) in Natal, Rio Grande do Norte, through its managers, professionals and users, having as its support the Theory of Belief and the Cognitive-Behavioral Theory. This is a multimethod research and is divided into three sub-studies. In the first study, nine managers answered to a semi-structured interview, to verify the knowledge and beliefs on SUS; the quantitative data were analyzed with descriptive statistics with the aid of SPSS software and the qualitative data were submitted to lexical analysis with support of ALCESTE software. In the second study, we have a descriptive correlational research in which the antecedent variables are related to working conditions in the family health units (FHUs) and to the professionals‟ profile; the corresponding variables refer to the evaluations of the FHS; a stratified probabilistic sample with 475 professionals, who answered to two scales, both consisting of three factors: Physical infrastructure, Material resources, and Treatment effectiveness, and data were analyzed using descriptive, bivariate and multivariate statistics, with the aid of SPSS. The third study is a descriptive correlational research in which the antecedent variables refer to the treatment in the FHUs and to the users‟ profile, and the corresponding variables refer to the evaluations of the FHS, with a stratified non-probabilistic sample with 390 users, who contributed to the construction of a new scale with a factor, effectiveness in treatment, analyzed through descriptive, bivariate and multivariate statistics, with the aid of SPSS. The results showed problems which start from management, under the shape of admission due to political indication and lack of knowledge on SUS and the FHS; they pass through the low tenure of professionals and insufficient professional; and they end up spreading all over the analyzed items: infrastructure of FHUs, material resources, professionals‟ training, accessibility and referral system. One concludes that, despite following an ideal model, the FHS is in need of changes with regard to the barriers to its operational reality